Research on comprehensive environmental impact assessment of shale gas development. Issue 1 (3rd February 2020) - Luo, Zhenhua; Chen, Yixi; Cen, Kang; Pan, Haize; Zhong, Mengfan; He, Jian
Abstract : Purpose: In recent years, to solve the contradiction between energy supply and demand, the Chinese Government has vigorously promoted shale gas development. With the rapid development of the shale gas industry, the environmental impact problems have become increasingly serious. Therefore, it is of great significance to carry out a comprehensive environmental impact assessment of shale gas development. This study aims to provide a theoretical basis for enterprises to make development decisions on shale gas projects by constructing a model of comprehensive environmental impact assessment for shale gas development. Design/methodology/approach: In this paper, the comprehensive environmental impact factors of shale gas development are analyzed from the two aspects of the natural environment and macro environment, and the index system of comprehensive environmental impact assessment for shale gas development including 7 secondary indicators and 24 tertiary indicators is constructed. Owing to the fact that qualitative indicators are difficult to quantify in the evaluation process, the method of intuitionistic fuzzy analytic hierarchy process (IFAHP) is adopted for evaluation. This method (IFAHP) can delicately describe the hesitancy degree of the decision-makers in the process of assigning a weight to the indicators, and make the weight assignment of each index more accurate. Furthermore, this method overcomes the shortcomings of the conventional methods, such as the complexity of calculation and the large amount of calculation. Findings: The evaluation model is applied to a shale gas platform drilling project in Southwest China. Based on the ratings from 13 experts, the comprehensive environmental impact assessment grade of this project is good, indicating that the shale gas development project is feasible. The result is basically in line with the actual situation. Originality/value: Based on the consideration of the natural environmental impacts of shale gas development, this paper also has considered the macro environmental impact of shale gas development, and has established the index system of comprehensive environmental impact assessment for shale gas development from the two aspects of the natural environment and macro environment. To overcome such difficulties as incomplete evaluation by decision-makers, cumbersome calculation process and a large amount of calculation, this paper has adopted the method of IFAHP to evaluate and has established a comprehensive environmental impact assessment model for shale gas development based on IFAHP.